2005
DOI: 10.1080/0013188042000337587
|View full text |Cite
|
Sign up to set email alerts
|

Children's opinions on effective strategies to cope with bullying: the importance of bullying role and perspective

Abstract: To cite this Article Camodeca, Marina and Goossens, Frits A.(2005) 'Children's opinions on effective strategies to cope with bullying: the importance of bullying role and perspective ', Educational Research, 47: 1,[93][94][95][96][97][98][99][100][101][102][103][104][105] To link to this Article: DOI: 10.1080/0013188042000337587 URL: http://dx.doi.org/10.1080/0013188042000337587Full terms and conditions of use: http://www.informaworld.com/terms-and-conditions-of-access.pdf This article may be used for researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
4
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 27 publications
5
89
4
6
Order By: Relevance
“…A number of investigators have argued that the development of more effective approaches to bullying prevention requires input from the students these programs are designed to influence [Booren and Handy, 2009;Camodeca and Goossens, 2005;Varjas et al, 2008]. Many teachers are not present when bullying occurs.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A number of investigators have argued that the development of more effective approaches to bullying prevention requires input from the students these programs are designed to influence [Booren and Handy, 2009;Camodeca and Goossens, 2005;Varjas et al, 2008]. Many teachers are not present when bullying occurs.…”
mentioning
confidence: 98%
“…Understanding the recommendations of students, therefore, is an important step in the program design process. Camodeca and Goossens [2005] asked students (average age 11) to rate the effectiveness of different responses to bullying. Although students categorized by peers as victims, defenders, or outsiders recommended that students respond nonchalantly or assertively, those categorized as bullies rated retaliation to be more effective.…”
mentioning
confidence: 99%
“…In a study of strategies to cope with bullying, Camodeca and Goossens (2005) found that children most frequently chose assertiveness. There were gender differences in the favoured responses: girls chose assertive strategies more often than boys.…”
Section: Craig Et Al: Responding To Bullyingmentioning
confidence: 99%
“…Στην περίπτωση της ΠΘ, έχει φανεί πως τα θύματα ενδέχεται να σημειώνουν μειωμένη επάρκεια ως προς τις στρατηγικές δια-χείρισης ψυχοπιεστικών καταστάσεων και περιορισμού της επιθετικότητας των συνομηλί-κων τους (Didaskalou et al, 2015). Αρνητικές εμφανίζονται και οι σχέσεις της κοινωνικής υποστήριξης με την ΠΘ , εύρημα που μπορεί να αποδοθεί σε δυσκολί-ες διαχείρισης της κατάστασης (Camodeca & Goossens, 2005) και σε κρίσεις περί επιδείνω-σης της κατάστασης με την παρέμβαση άλλων (Kanetsuna & Smith, 2002). Επιπλέον, βρέθη-κε αρνητική συσχέτιση του συμπεριφορικού εκφοβισμού και του έμμεσου εκφοβισμού σχέ-σεων με τον μηρυκασμό ιδεών .…”
Section: στρατηγικές διαχείρισης ψυχοπιεστικών καταστάσεωνunclassified